Phenotypic characterisation of the monocyte subpopulations in healthy adult pigs and Salmonella-infected piglets by seven-colour flow cytometry - Ondrackova, Petra; Matiasovic, Jan; Volf, Jiri; Dominguez, Javier; Faldyna, Martin (Research in veterinary science, 2013)
The present study describes the distinct bone marrow (BM) and peripheral blood (PB) monocyte subpopulations detected by seven-colour flow cytometry. Mononuclear phagocytes were identified as viable CD172a(+) SWC8(-) CD203a(-) mononuclear leukocytes. After that, monocyte subpopulations were differentiated by using CD14, CD163 and SLA-DR markers. Four distinct monocyte subpopulations were found in the BM and PB. Based on the discovered populations two possible maturation pathways have been proposed. The first pathway was characterised by release of CD14(hi) CD163(-) SLA-DR(-) BM monocytes into the PB where they matured into CD14(low) CD163(+) SLA-DR(+) monocytes. In the alternative pathway the monocytes finalised their phenotypical maturation in the BM and then they were released into the PB as CD14(low) CD163(+) SLA-DR(+) cells. In Salmonella-infected piglets, the population of CD14(low) CD163(+) SLA-DR(+) monocytes was elevated in the BM and mesenteric lymph nodes (MLN), suggesting the role of this population in pathogenesis of Salmonella infection in pigs.
Keywords: Animals; buňky kostní dřeně; Salmonella enteritidis; Membrane Proteins; Salmonella Infections, Animal; zvířata; Monocytes; Flow Cytometry; monocyty; salmonelová infekce u zvířat; prasata; nemoci prasat; průtoková cytometrie; membránové proteiny; Swine; Swine Diseases; Bone Marrow Cells